Sequential Changes in the Host Gut Microbiota During Infection With the Intestinal Parasitic Nematode Strongyloides venezuelensis - Afrin, Tanzila; Murase, Kazunori; Kounosu, Asuka; Hunt, Vicky L.; Bligh, Mark; Maeda, Yasunobu; Hino, Akina; Maruyama, Haruhiko; Tsai, Isheng J.; Kikuchi, Taisei (Frontiers in Cellular and Infection Microbiology, 2019)
Soil-transmitted helminths (STHs) are medically important parasites that infect 1.5 billion humans globally, causing a substantial disease burden. These parasites infect the gastrointestinal tract of their host where they co-exist and interact with the host gut bacterial flora, leading to the coevolution of the parasites, microbiota and host organisms. However, little is known about how these interactions change through time with the progression of infection. Strongyloidiasis is a human parasitic disease caused by the nematode Strongyloides stercoralis infecting 30–100 million people. In this study, we used a closely related rodent parasite Strongyloides venezuelensis and mice as a model of gastrointestinal parasite infection. We conducted a time-course experiment to examine changes in the faecal microbiota from the start of infection to parasite clearance. We found that bacterial taxa in the host intestinal microbiota changed significantly as the infection progressed, with an increase in the genera Bacteroides and Candidatus Arthromitus, and a decrease in Prevotella and Rikenellaceae. However, the microbiota recovered to the pre-infective state after parasite clearance from the host, suggesting that these perturbations are reversible. Microarray analysis revealed that this microbiota transition is likely to correspond with the host immune response. These findings give us an insight into the dynamics of parasite–microbiota interactions in the host gut during parasite infection.